Maternal, perinatal and childhood outcomes of the PPROMEXIL-III cohort: Pregnancies complicated by previable prelabor rupture of membranes. (October 2021) - Simons, Noor E.; de Ruigh, Annemijn A.; van der Windt, Larissa I.; Kazemier, Brenda M.; van Wassenaer-Leemhuis, Aleid G.; van Teeffelen, Augustinus S.; van Leeuwen, Elisabeth; Mol, Ben Willem; van 't Hooft, Janneke; Pajkrt, Eva
Abstract: Objective: Perinatal mortality after previable prelabor rupture of membranes (previable PROM) might be underestimated as most studies exclude patients with poor prognosis, or solely include patients in tertiary-care centers. We aimed to report perinatal, neonatal and long-term outcomes in a consecutive series of women with pregnancies complicated by previable PROM. Study design: We conducted a prospective cohort study including women with singleton pregnancies and previable PROM ≤ 23 +6 weeks gestational age (GA) from one tertiary hospital and eight affiliated secondary hospitals in the region of Amsterdam, the Netherlands (June 2012 until January 2016, PPROMEXIL-III cohort). Exclusion criteria were signs of active labor before onset of PROM or fetal structural anomalies visible at ultrasound. We assessed perinatal mortality. Furthermore, outcomes were maternal, perinatal, neonatal and long-term child characteristics. Results: We included 98 pregnancies with previable PROM. Twelve women (12.2%) opted for termination of pregnancy, resulting in 86 pregnancies included in further analyses. Median GA at PROM was 20 +2 weeks (interquartile range (IQR) 17 +6 -22 +0 ). Median GA at delivery was 22 +6 weeks (IQR 20 +1 -26 +4 ). Delivery within 1 week occurred in 38.4% of women and 60.4% delivered before 24 weeks GA (viability). Perinatal mortality occurred in 73.3% of pregnancies. 23/33 (69.7%) live-born neonates survived to discharge, representing 26.7% of total. None of the children died after discharge. Developmental data at two and/or five years of age was available for 13/23 children (i.e. all children born before 32 weeks of gestation), with 69.2% of children reporting a normal neurodevelopment. However, more than half of children reported respiratory problems. Conclusion: In women with previable PROM perinatal mortality was 73.3%, with a normal neurodevelopment in 69.2% of surviving children with follow-up data. Due to broad inclusion criteria, this cohort represents a population more generalizable to daily practice as compared to previous studies.